2016
DOI: 10.1002/med.21392
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on Volasertib: Preclinical and Clinical Evaluation of a Promising Plk1 Inhibitor

Abstract: Considering the important side effects of conventional microtubule targeting agents, more and more research focuses on regulatory proteins for the development of mitosis-specific agents. Polo-like kinase 1 (Plk1), a master regulator of several cell cycle events, has arisen as an intriguing target in this research field. The observed overexpression of Plk1 in a broad range of human malignancies has given rise to the development of several potent and specific small molecule inhibitors targeting the kinase. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 112 publications
(313 reference statements)
2
71
1
1
Order By: Relevance
“…This is consistent with the results of clinical trials of treatment with PLK1 inhibitors in patients with solid tumors, which demonstrated striking clinical responses but low response rates (4–14%) and stable disease rates of 26–42% in unselected patients [41, 4548, 53, 60]. Up to 11% of patients had stable disease for more than a year [45, 48].…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the results of clinical trials of treatment with PLK1 inhibitors in patients with solid tumors, which demonstrated striking clinical responses but low response rates (4–14%) and stable disease rates of 26–42% in unselected patients [41, 4548, 53, 60]. Up to 11% of patients had stable disease for more than a year [45, 48].…”
Section: Discussionsupporting
confidence: 86%
“…It should be noted that several kinase inhibitors have been administrated as an iv infusion in clinical trials [39]. For example, volasertib, an intravenous polo-like kinase (PLK) inhibitor, is currently in phase III for the treatment of AML [40]. A phase II/III trial using barasertib (an intravenous AURKB inhibitor) alone and in combination with low dose cytosine arabinoside has been completed in AML [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical experiments have demonstrated that BI6727 is highly efficacious in inducing tumor regression [116], [132], [133], [134]. As a result, this agent has recently been awarded the “Breakthrough Therapy Status” by the Food and Drug Administration for its significant benefit in treating acute myeloid leukemia patients [135]. However, because of the high conservation of ATP binding domains of different kinases and the frequent mutation in ATP binding sites, cancer patients always develop resistance to ATP -competitive inhibitors [136].…”
Section: Plk1 and Human Cancermentioning
confidence: 99%